2019
DOI: 10.1002/dev.21946
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and performance‐related differences in source memory retrieval during early childhood: Insights from event‐related potentials

Abstract: Across early childhood, children's ability to remember individual items and the details that accompany these items (i.e., episodic memory) improves greatly. Given that these behavioral improvements coincide with increases in age, effects of age and performance are often confounded. This study used event‐related potentials (ERPs) to investigate age‐ and performance‐related differences in the neural processes underlying the development of memory for details during early childhood. Using a source memory paradigm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…However the location of this effect differed between the age groups, moving from frontal parietal leads in 3-year olds to the left hemisphere leads in 4 year olds [ 74 ]. However, another study found no association between Nc in the frontal and central electrodes and age when comparing children younger than 5.8-years with older ones [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…However the location of this effect differed between the age groups, moving from frontal parietal leads in 3-year olds to the left hemisphere leads in 4 year olds [ 74 ]. However, another study found no association between Nc in the frontal and central electrodes and age when comparing children younger than 5.8-years with older ones [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies of older children typically assess the FN400 and parietal old/new effect (e.g., Cycowicz et al., 2001; Czernochowski et al., 2009; Czernochowski et al., 2005; Mecklinger et al., 2011; Rollins & Riggins, 2018; Sprondel et al., 2011, 2012). However, due to differences in the morphology of ERP waveforms observed in younger children, studies of early childhood typically assess the negative component (Nc) and late slow wave (LSW; Canada et al., 2020; Riggins & Rollins, 2015; Riggins et al., 2013). The Nc occurs approximately 350−800 ms and is typically maximal over frontal and central electrodes (for review, see DeBoer et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, ERP tasks for toddlers and preschool‐aged children typically last approximately 10–15 min (Brooker et al., 2020; see Howard et al., 2020, for empirical example). One approach to minimize recording durations for recognition memory research has been to selectively record electroencephalography (EEG) only during encoding or retrieval (Canada et al., 2020; Geng et al., 2018; Riggins & Rollins, 2015; Riggins et al., 2013; Robey & Riggins, 2016; Rollins & Riggins, 2013, 2018) or divide encoding and retrieval across multiple testing sessions (e.g., Leventon et al., 2014). However, studies of children 7 years of age and older have been successful collecting EEG data for both encoding and retrieval during a testing session lasting approximately 2 h (Czernochowski et al., 2005, 2009; Haese & Czernochowski, 2016; Mecklinger et al., 2011; Sprondel et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERP recollection‐based processing indices have also been documented in children. For example, the parietal EM effect has been observed in older school‐aged children (Czernochowski et al., 2005; de Chastelaine et al., 2007), whereas in younger preschool‐aged children a late‐slow wave component is associated with both the encoding (Geng et al., 2018) and retrieval of contextual details (Canada et al., 2019; Riggins et al., 2013).…”
Section: Introductionmentioning
confidence: 99%